Mutual Fund Performance in the Southeast Asian Market: Evidence for Malaysia, Thailand And Vietnam - Nguyen, Phuong Thang (2018)
The study investigates the performance of equity mutual funds in the Southeast Asian market which is represented by Malaysia, Thailand and Vietnam during the period from January 2012 to December 2017. On average, Malaysian equity mutual funds underperformed the market whereas equity mutual funds in Thailand performed better than the market. In Vietnam, equity mutual funds insignificantly underperformed market index benchmark. The finding also reveals that fund managers in Malaysia prefer small-cap stocks while Vietnamese and Thai managers prefer large-cap stocks. Furthermore, evidence of value stock oriented was found in Vietnam whereas Thai mutual fund market was growth stock oriented, insignificant value premium was documented for Malaysia. Regarding timing ability, no evidence of timing skill was found in Thai market, meanwhile both Vietnamese and Malaysian fund managers possessed negative timing skills.